Having visions : the Book of Mormon translated and exposed in plain English - Wolverton, Susan Stansfield (Algora Pub., 2004)
The archaic Elizabethan dialect and vocabulary in which The Book of Mormon was originally written is cumbersome to read and difficult to understand for 21st-century readers, making the language itself a barrier to knowing its content. While both the Bible and The Book of Mormon are written in a similar dialect, one reads like poetry and the other reads like a repetitive textbook. In Having Visions, the author presents an objective, respectful, and faithful translation of its content, accompanied with an historical and scientific context for understanding its insertion into the body of human affairs. In The Book of Mormon, the ancient American prophet Mormon presents the history of his people, the Nephites. The intent of the present book is to present "his story as told," and its relationship to "history as known," without altering its essence. Early readers of this translation have commented on the cardboard characters, the superficial story line and the repetitious narrative. "The battle scenes lack drama and suspense," they've said. "Your writing drones on like a grade-school text book." The fact is, that's the way The Book of Mormon presents the material. Having Visions seeks to trace the narrative through a bewildering stream of verbiage (without straying from a function of translation into analysis), but many sections remain confused; to add drama and elegance of language would be to introduce elements that just are not there. Other readers have been mystified by the inconsistencies in tense, style and narration; Mormon authorities explain them by noting that The Book of Mormon compiles the writings of 27 different authors, later abridged by two different editors before Joseph Smith. It should be noted that exhaustive archeological, genetic, and linguistic research has been undertaken by both proponents for, and detractors of, the existence of the Nephites. So far, no evidence supporting the claim has ever been found for any place, person, or event mentioned in The Book of Mormon, while abundant contradictory evidence has been discovered and independently verified. Susan Stansfield Wolverton is a pen name.